1997
DOI: 10.2223/jped.497
|View full text |Cite
|
Sign up to set email alerts
|

A study on protozoan cysts, helminth eggs and larvae in pacifiers

Abstract: ResumoObjetivo: Devido à alta prevalência das enteroparasitoses entre crianças no Brasil e do possível envolvimento de objetos na transmissão dessas doenças, foi desenvolvido um estudo para pesquisar a presença de cistos de protozoários, larvas e ovos de helmintos em chupetas.Métodos: No período de março a dezembro de 1993, foram examinadas 86 chupetas de crianças na faixa etária de zero a sete anos, residentes no bairro Vila Promessa, município de Alfenas, MG. A pesquisa de cistos, larvas e ovos foi realizada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…However, silicone pacifiers still have potential for microorganism adhesion and can be a considerable source of infection, as endorsed by previous studies. The present study showed that a wide variety of reference strains ( S. mutans, S. pyogenes, E. coli, C. albicans and S. aureus ) is able to grow and to form biofilms in this surface.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…However, silicone pacifiers still have potential for microorganism adhesion and can be a considerable source of infection, as endorsed by previous studies. The present study showed that a wide variety of reference strains ( S. mutans, S. pyogenes, E. coli, C. albicans and S. aureus ) is able to grow and to form biofilms in this surface.…”
Section: Discussionsupporting
confidence: 74%
“…Silicone is less prone to microbial Antimicrobial solutions in spray for biofilm pacifiers 583 colonization and has lower allergenic potential in comparison to latex pacifiers [4][5][6][7] . However, silicone pacifiers still have potential for microorganism adhesion and can be a considerable source of infection, as endorsed by previous studies 6,7,14,16 . The present study showed that a wide variety of reference strains (S. mutans, S. pyogenes, E. coli, C. albicans and S. aureus) is able to grow and to form biofilms in this surface.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Children between the ages of seven and ten demonstrated the greatest vulnerability to ascariasis infection. Results from this study corroborate those of other studies such as Pedersso and Siqueira (1997) in Brazil; Blumenthal et al (2001) in Mexico and Verle et al (2003) in Northern Vietnam.…”
supporting
confidence: 92%
“…A few authors have searched for specific microbial species on pacifiers. Pedroso and Siqueira (1997) demonstrated that pacifiers were an important source of infection by intestinal parasites, such as protozoan cysts and helminth eggs or larvae. Mattos-Graner et al (2001) found a relationship between the use of a pacifier and the proliferation of yeast in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%